IL-1β enhances cell viability and decreases 5-FU sensitivity in novel colon cancer cell lines derived from African American patients - Spagnardi, Marzia; Paredes, Jenny; Zabaleta, Jovanny; Garai, Jone; Reyes, Tiana; Martello, Laura A.; Williams, Jennie L. (Frontiers in Oncology, 2022)
Background: In the U.S., African Americans (AAs) present with the highest incidence and mortality rates for Colorectal Cancer (CRC). When compared to Caucasian American (CA) patients, AAs also have reduced response to the first line standard of care chemotherapeutic agent 5-Fluorouracil (5-FU). Previously, we observed differential gene expression between the two populations, suggesting that colon tumors from AA patients display a decreased antitumor immune response and an increased expression of genes encoding proteins involved in inflammatory processes, such as Interleukin-1β (IL-1β). Here, we investigate the role of IL-1β in modifying chemotherapeutic response and altering expression of proteins in novel AA and well-established CA colon cancer cell lines. Methods: RNA sequencing analysis was performed to detect expression of genes involved in inflammation in AA and CA colon cancer cells. The effects of IL-1β on 5-FU response was evaluated by assessing cell viability (MTS assay) and apoptosis (flow cytometry analysis) following treatment with 5-FU alone or in combination with the cytokine. Further, we used an IL-1 receptor antagonist (IL-1Ra) to inhibit IL-1β-induced effects on 5-FU sensitivity and NF-kB pathway activation. Results: AA colon cancer cell lines present significant increase in expression of genes IL1R2 (373-fold change (FC)), IRAK1 (3.24 FC), IKBKB, (5.33 FC) NF-ΚB IA (5.95 FC), MYD88, (3.72 FC), IRAK3 (161 FC), TRAF5 (4.1 FC). A significant decrease in the response to 5-FU treatment, as well as a significant increase in phosphorylation of IκBα and secretion of IL-8, was seen following IL-1β treatment, in both AA and CA cell lines. Finally, treatment with IL-1Ra was able to reverse the effects induced by IL-1β, by increasing the cells sensitivity to 5-FU. IL-1Ra also inhibited phosphorylation of IκBα and IL-8 secretion. Conclusions: Our results suggest a differential expression of inflammatory genes and proteins that might regulate the different response to IL-1β between AA and CA colon cancer cell lines. Our data also demonstrates that IL-1β is involved in modulating 5-FU response in both AA and CA colon cancer cell lines. Further investigation of these mechanisms might help elucidate the differences seen in incidence, mortality and response to therapy in AA colon cancer patients.